Never the right age: Age discrimination in recruitment and selection in Portugal - Vinha, M.; Sousa, I.C. (22nd Congress of the European Association of Work and Organizational Psychology (EAWOP), 2025)
The aging Portuguese population and rising legal retirement age have led to a more age-diverse workforce. This study investigates age discrimination in Recruitment and Selection (R&S) processes in Portugal from the perspective of recruiters. It also examines whether recruiters’ stereotypical views of younger and older candidates affect hiring decisions. We conducted 22 semi-structured interviews with recruiters from various organizations in Portugal. As part of the interviews, participants completed an exercise evaluating CVs for a hypothetical vacancy. The data was analyzed using content analysis in MAXQDA. Findings indicate that age discrimination persists in R&S processes in Portugal, affecting both younger and older candidates implicitly. Recruiters continue to prioritize criteria such as seniority, experience, and specific skills that tend to prejudice younger candidates. At the same time, recruiters can identify and expose the presence of age discrimination in R&S practices as defined by organizations. Furthermore, although older workers are generally viewed more favorably than younger ones, this does not translate into actual hiring decisions, where older candidates face ongoing discrimination. Motives for discriminating against older candidates include high salary expectations, proximity to retirement, and perceived higher training costs. This study contributes to the literature on age discrimination by addressing the treatment of younger and older candidates during R&S processes. It also provides insights for organizations to reduce the impact of age-related factors in recruitment, such as training recruiters to adopt age-sensitive practices.